A study on sources of Waqf funds for higher education in selected countries - Abdul Razak, Dzuljastri; Che Embi, Nor Azizan; Che Mohd Salleh, Marhanum; Fakhrunnas, Faaza (2016)
The waqf concept has nowadays been utilized to meet various purposes including housing, poverty alleviation, financingand also for education. In general, the ultimate aim of the waqf concept is to bring benefit to the society. This study aims at reviewing literatures on the sources of waqf funds for higher education in selected countries such as Malaysia, Indonesia, Turkey and United Kingdom. Adopting the content analysis methodology, it is found that there are significant numbers of waqf and endowment-based universities that have implemented the waqf principle in their education system. Nonetheless, they have their own unique mechanism. This studyalso observed that waqf fund hassuccessfully upgraded the education system in these countries and provides opportunity for the poorand needy. Hence, it is suggested that the waqf board of higher education institutions further promote the utilization of waqf as it brings fairness and benefits to society.